Learning English "Ways to Improve University Students' Vocabulary - Meung, Hluing; Htut, Myet (Educia Journal, 2023)
This article discusses about ways to improve University Students' Vocabulary. The importance of students' vocabulary skills and understanding to support student skills in aspects of the English language. The aim of writing this article is to develop language skills both orally and in writing. The skills referred to are how we listen, speak, read, understand and write. Because the four skills are a unity that is bound and one with each other and we cannot separate them but can be distinguished.